International Journal of Practical Theology (De Gruyter, 1997)
The journal publishes contributions to an empirical-descriptive and critical-constructivist theory of the Church and religious practices. A guiding concept is a broad understanding of religious practice that examines diverse forms of lived religion as they relate to the normative self-concept of churches, ecclesiastical groups, and denominations.